2013
DOI: 10.1007/s00246-013-0671-y
|View full text |Cite
|
Sign up to set email alerts
|

Tolvaptan Increases Serum Sodium in Pediatric Patients With Heart Failure

Abstract: This study aimed to evaluate the use of tolvaptan in a consecutive series of pediatric patients with heart failure. Patients 18 years of age or younger with heart failure prescribed tolvaptan between January 2009 and October 2011 were retrospectively identified at Children's Medical Center Dallas. Laboratory parameters, urine output, fluid balance, and concurrent medications were recorded at baseline and at specified intervals after a single dose of tolvaptan. The 28 patients in the study had a median age of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…Tolvaptan has been reported in a case series of 28 paediatric patients with heart failure (8), a patient with restrictive cardiomyopathy (9) and a patient with massive oedema due to nephrotic syndrome (10). In these paediatric case reports and case series, tolvaptan was well tolerated and considered to be a safe treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Tolvaptan has been reported in a case series of 28 paediatric patients with heart failure (8), a patient with restrictive cardiomyopathy (9) and a patient with massive oedema due to nephrotic syndrome (10). In these paediatric case reports and case series, tolvaptan was well tolerated and considered to be a safe treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Experience with vaptans is limited in children. In a single-center, retrospective, uncontrolled study in 28 pediatric heart failure patients hospitalized with heart failure, treatment with tolvaptan was associated with increased serum sodium levels and greater urine output (158). More data are needed to determine the safety and efficacy of vaptans in pediatric cardiac patients.…”
Section: Vaptansmentioning
confidence: 95%
“…Other studies have shown that the continuous perfusion of 0.01–0.03 µg/kg/min nesiritide improves echocardiogram variables (heart rate, left ventricular ejection fraction) and laboratory values (decreased creatinine, BNP and aldosterone levels) after 72 h [ 26 ]. In a retrospective series of 28 children with heart failure and hyponatremia, tolvaptan, a selective non-peptide antagonist the arginine vasopressin receptors (V2), improved, when used orally at a dose of 0.3 mg/kg, both diuresis and sodium levels after 72 h [ 27 ].…”
Section: Field Of Application 2: Patient Pathway Management Principlmentioning
confidence: 99%